The obesity-related single nucleotide polymorphisms FTO and GHSR genes and the postprandial feeling of fullness in Filipino adults - Nacis, Jacus S.; Golloso-Gubat, Ma. Julia; Magtibay, Edward Vincent J.; Udarbe, Mildred A.; Santos, Noelle Lyn C. (2018)
Obesity-related single nucleotide polymorphisms (SNPs) may impact the control of energy intake and eating behavior. However, the effect size of those individual SNPs is not yet fully elucidated. Intervention studies using a standardized test meal coupled with a validated visual analogue scale (VAS) is important in understanding the influence of SNPs in the subjective feeling of appetite. This study aimed to assess the influence of obesity-related SNPs on appetite responses of Filipino adults following consumption of equicaloric breakfast meals. In an intervention study, thirty-four apparently healthy Filipino adults were genotyped for SNPs in the fat mass and obesity-associated gene (FTO) and growth hormone secretagogue receptor (GHSR). A validated VAS was used to capture the pre- and post-prandial feeling of the appetite of the study participants. Analysis of covariance (ANCOVA) was used to determine the differences between the subjective ratings of appetite (hunger, fullness, desire to eat, and prospective consumption) relative to the genotype of the study participants. The mean rating of fullness was 5.6% lower in carriers of the risk-allele A for FTO rs9939609 and 16.6% higher in carriers of the risk-allele A for GHSR rs572169. The levels of fullness after a meal is significantly influenced by the obesityrelated SNPs FTO rs9939609 and GHSR rs572169 after controlling for age, sex, height, weight, BMI, and baseline appetite scores of the study participants. Our result implies that genetic polymorphisms might pose control of subsequent food intake.